2022
DOI: 10.2337/dc21-1693
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Socioeconomic Environment and Risk of Type 2 Diabetes: Associations and Mediation Through Food Environment Pathways in Three Independent Study Samples

Abstract: OBJECTIVE We examined whether relative availability of fast-food restaurants and supermarkets mediates the association between worse neighborhood socioeconomic conditions and risk of developing type 2 diabetes (T2D). RESEARCH DESIGN AND METHODS As part of the Diabetes Location, Environmental Attributes, and Disparities Network, three academic institutions used harmonized environmental data sources and analytic methods in thre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…However, several longitudinal cohort studies 7,8 define diabetes using a combination of ICD codes and medications as well as in analyses using electronic medical record (EMR) data. 8,12 Varying definitions of diabetes can lead to different estimated impacts on outcomes 12 in studies using EMR data, and findings that suggest substantial differences in patterns of prescribing diabetes medications by Medicare plan type. 6 It is important to point out that our examination of the data is not without limitations and should only serve as a prompt for awareness for other investigators.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several longitudinal cohort studies 7,8 define diabetes using a combination of ICD codes and medications as well as in analyses using electronic medical record (EMR) data. 8,12 Varying definitions of diabetes can lead to different estimated impacts on outcomes 12 in studies using EMR data, and findings that suggest substantial differences in patterns of prescribing diabetes medications by Medicare plan type. 6 It is important to point out that our examination of the data is not without limitations and should only serve as a prompt for awareness for other investigators.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies using Medicare claims data define diabetes only using ICD codes 2,3 or ICD code-derived algorithms, 4,5 and thus may not be sensitive to the changing indications for the use of diabetesrelated medications over time. However, several longitudinal cohort studies 7,8 define diabetes using a combination of ICD codes and medications as well as in analyses using electronic medical record (EMR) data. 8,12 Varying definitions of diabetes can lead to different estimated impacts on outcomes 12 in studies using EMR data, and findings that suggest substantial differences in patterns of prescribing diabetes medications by Medicare plan type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4–8 In an analysis of three study samples in the USA, greater socioeconomic disadvantage was generally associated with higher relative risk of T2D across study samples in most community types ranging from rural to urban in the Diabetes Location, Environmental Attributes, and Disparities (LEAD) Network. 9 Stark geographic disparities in the incidence and prevalence of T2D observed across regions, counties, and neighborhoods may be attributable to community-level structural causes. 10–14 …”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies have found graded associations between greater area-level socioeconomic disadvantage, despite differences in measurement, and higher risk of type 2 diabetes (T2D) across a variety of study populations and designs 4–8. In an analysis of three study samples in the USA, greater socioeconomic disadvantage was generally associated with higher relative risk of T2D across study samples in most community types ranging from rural to urban in the Diabetes Location, Environmental Attributes, and Disparities (LEAD) Network 9. Stark geographic disparities in the incidence and prevalence of T2D observed across regions, counties, and neighborhoods may be attributable to community-level structural causes 10–14…”
Section: Introductionmentioning
confidence: 99%